2007
DOI: 10.1892/0891-6640(2007)21[526:doapda]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of a Patent Ductus Arteriosus with Right Heart Failure in an Adult Dog

Abstract: A 3-year-old male, castrated, miniature pinscher weighing 9 kg was presented to the University of Zurich Veterinary Teaching Hospital Cardiology Service for evaluation of lethargy, a newly recognized cardiac murmur, and labored breathing. For the previous 3 days, the dog had been progressively reluctant to move and breathing had become labored. Before the current presentation, the dog had always been in excellent health.On admission, the dog was in sternal recumbency, profoundly lethargic, and showed expirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Pulmonary artery dissection is a very unusual finding in veterinary medicine, since it has only been reported in dogs [6,7,8,9] and cattle [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary artery dissection is a very unusual finding in veterinary medicine, since it has only been reported in dogs [6,7,8,9] and cattle [8].…”
Section: Discussionmentioning
confidence: 99%
“…University of Turin's Institutional Research Information System and Open Access Institutional Repository with patent ductus arteriosus [6,9] or anomalous vessels [8] is considered the main predisposing cause in dogs. Marfan's syndrome [10] and secondary degenerative cystic wall changes [9] are also reported as underlying causes in cattle and dogs, respectively.…”
Section: Iris-apertomentioning
confidence: 99%
See 1 more Smart Citation
“…31 The authors are aware of 4 cases reported in the literature describing pulmonary artery dissections in dogs. 6,10e12 In the first 3 cases, the pulmonary artery dissection was associated with a concurrent aortic dissection either traversing a PDA, 10 spanning the ligamentum arteriosum, 11 or communicating in an uncertain location. 6 In the most recent report, the pulmonary artery dissection was associated with an anomalous vessel between the ascending aorta and main pulmonary artery, the embryology of which was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Three prior descriptions of pulmonary artery dissection in the dog have all been associated with concurrent aortic dissection. 6,10,11 Recently, a pulmonary artery dissection was appreciated in a dog with an anomalous vessel between the ascending aorta and main pulmonary artery. 12 The aim of this case series is to describe pulmonary artery dissection in 8 dogs, each with a patent ductus arteriosus (PDA).…”
Section: Introductionmentioning
confidence: 99%